Flow measurements at drop structures for irrigation system management in Sri Lanka - Sakthivadivel, Ramaswamy; Merrey, Douglas J. (International Irrigation Management Institute, 1992)
The method suggested in this manual provides a simplified procedure for calibrating and/or updating drop structure curves. The convenience of the proposed method outweighs the lack of rigor and precision, and in any event, the resulting degree of accuracy appears sufficient for most operational purposes.